A CONTENT ANALYSIS OF THE ENGLISH READING TEXT’S AUTHENTICITY IN STUDENT’S BOOK OF ACTION PACK ELEVEN IN JORDAN - Al-Ghazo, Abeer; M.Smadi, Oqlah (European Scientific Journal, ESJ, 2013)
Based on the specific reading outcomes under the Reading Section in the General Guidelines and General and Specific Outcomes for English Language in Jordan of 2006, the present paper aims at analyzing the reading texts of the student’s book in Action Pack Eleven to determine to what extent the reading texts are authentic. Frequencies and Percentages are used to present the results of the question of the study. The findings of the analysis revealed that the reading texts of the student’s book in Action Pack 11 have a high degree of authenticity. There is a strong match between reading specific outcomes and the reading text’s authenticity in Action Pack Eleven. Such focus on authentic reading texts highlights the significance of the reading skill in building the communicative competence of the Jordanian students at the secondary stage.